Układ outsourcingowy jako rodzaj sieci międzyorganizacyjnej - Niemczyk, Jerzy (Outsourcing Networks - towards Interorganizational Networks, 2006)
Future belongs to a network. However, "the rules of efficient and effective network management are just emerging" [Koźmiński 2004] Outsourcing networks are a kind of interorganizational networks. The goal of the paper is to present the arguments for treating outsourcing networks as some kind of interorganizational network as well as a way of implementing company's network strategy.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1104, s. 345-350